Do Interest Rates Matter? Credit Demand in the Dhaka Slums - Rajeev H. Dehejia; Heather Montgomery; Jonathan Morduch (Asian Development Bank Institute (ADBI), 2005)
If the demand for credit by the poor changes little when interest rates increase, lenders can raise fees to cost-covering levels without losing customers. This claim is at the core of sustainable microfinance strategies that aim to provide banking services to the poor while eschewing long-term subsidies. However, so far, there is little direct evidence that this is true. This paper uses data from SafeSave, a credit cooperative in the slums of Dhaka, Bangladesh, to examine how sensitive borrowers are to increases in the interest rate on loans. Using unanticipated between-branch variation in the interest rate, we estimate interest elasticities of loan demand ranging from –0.73 to –1.04. Less wealthy account holders are more sensitive to the interest rate than (relatively) wealthier borrowers (an elasticity of –0.86 compared to –0.26), and consequently the bank's portfolio shifts away from its poorest borrowers when it increases the interest rate.
hdl:11540/4175
Keywords: 330